In–situ Synthesizing and Optimizing the Surface Structure of Nanoporous PtBi Electrocatalysts for Formic Acid Electro–oxidation. Issue 4 (8th February 2017) - Yang, Yanfei; Yin, Huiming; He, Meifeng; Pan, Deng
Abstract: Aiming at the effect mechanism of bismuth species on Pt in formic acid oxidation reaction, different coverages of Bi adatoms on nanoporous Pt electrocatalyst surfaces are controllably prepared under the protection of hydrogen gas. Owing to Bi dissolution, in‐situ potential cycling in formic acid solution can successively increase surface Pt/Bi molar ratios, and hence influence the electrocatalytic activity towards formic acid oxidation. In particular, the optimized PtBi electrocatalyst shows about 100 times higher catalytic activity than that of commercial Pt/C catalyst. By integrating the results from electrochemical detection, this enhancement is ascribed to "third body" effect. Abstract : Different coverages of Bi adatoms on nanoporous Pt electrocatalyst surfaces are controllably prepared through an artful in‐situ method. By adjusting surface Pt/Bi molar ratios, the PtBi synergetic effect on electrocatalytic activity towards formic acid oxidation is investigated and ascribed to the "third‐body" mechanism. In particular, the optimized PtBi catalyst shows about 100 times higher catalytic activity than that of commercial Pt/C.